Formulation and Organoleptic Evaluation of Moringa Leaf (Moringa oleifera) Crackers as an Innovative Nutritious Snack - Fadila am. Latoriri; Abd. Hakim Langgeng; Musdalifah Nurdin; Lilies; Abdul Ashari; Masrianih (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the effect of moringa leaf flour addition at concentrations of 0%, 5%, 10%, and 15% on the sensory quality of crackers and to identify the most acceptable formulation based on consumer preference. The study employed a Completely Randomized Design (CRD) with three replications. Organoleptic evaluation was conducted with 30 untrained panelists using a 5-point hedonic scale to assess color, aroma, taste, and texture. The data were analyzed using one-way analysis of variance (ANOVA), followed by Tukey’s HSD test at a significance level of α = 0.05. The results showed that moringa leaf flour addition had a significant effect on all organoleptic attributes (p < 0.05). The formulation containing 10% moringa leaf flour showed the most balanced sensory profile, with mean hedonic scores of 3.60 for aroma, 3.47 for texture, 3.10 for taste, and 3.03 for color. These scores ranged from neutral to approaching like, indicating that the 10% formulation was relatively the most acceptable formulation compared with the other treatments.